Wearable cardioverter defibrillator after ICD-system explantation: data from a multicenter registry - El-Battrawy, Ibrahim; Beiert, Thomas; Koepsel, Katharina; Kovacs, Boldizsar; Dreher, Tobias C.; Blockhaus, Christian; Tenbrink, David; Klein, Norbert; Kuntz, Thomas; Lapp, Hendrik; Shin, Dong-In; Abumayyaleh, Mohammad S. A.; et al. (Scientific reports, 2025)
Data on the use of the wearable cardioverter defibrillator (WCD) among patients after cardiac implantable electronic device explantation of 1- to 3-chamber implantable cardioverter defibrillator systems (ICD) are sparse. Accordingly, several guidelines give a different recommendation regarding WCD indication in this cohort. We aimed to study the baseline characteristics and outcome of patients treated with WCD after ICD explantation. The primary outcome is appropriate WCD shock. Within a multicenter registry 109 patients received a WCD to bridge the time after ICD-system explantation until reimplantation due to a persistent ICD-indication. The mean follow-up was 824 ± 773 days. In addition to ventricular tachyarrhythmias and/or WCD shocks during WCD wear time, also the rate of rehospitalization for ventricular tachyarrhythmias, atrial fibrillation, stroke and congestive heart failure after ICD-reimplantation was evaluated. Patients had a mean age of 65 ± 14 years, and were hospitalized for 21 ± 15 days. The index left ventricular ejection fraction (LVEF) was at baseline 35.7 ± 14.1% and 35.7 ± 14.2% at short-term follow-up. Mean wear time of the WCD was 61 ± 46 days after ICD-system explantation. During that time an appropriate WCD shock was documented in 7.3% of patients. Up to 80.6% of patients after ICD-system explantation were re-implanted. The rates of rehospitalization due to ventricular tachyarrhythmias, heart failure and atrial fibrillation were 7.3%, 6.8% and 4.1%, respectively. After ICD-reimplantation the rate of appropriate shocks was 12/89 (13.4%). Occurrence of malignant ventricular tachyarrythmia after ICD-system explantation is high and the use of WCD among these patients could be beneficial in preventing sudden cardiac death.